2000
DOI: 10.1089/107999000312513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interleukin-15 onIn VitroHuman T Cell Proliferation and Activation

Abstract: Interleukin-15 (IL-15) has been reported to have many activities on T cell populations, including a potential role in improving antigen-specific proliferation in HIV-1 disease. We tested this response in healthy adults by studying the response of T cell populations after stimulation with medium, tetanus, cytomegalovirus (CMV) antigens in cultures from 21 volunteers. IL-15 caused a dose-dependent increase in medium and antigen-induced proliferation. The expansion was due to CD8>natural killer (NK)>CD4 lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…IL-15 induces lymphocyte proliferation and protects cells from apoptosis, thereby generating memory T cells (28) and anti-IL-15 can down-modulate lymphocyte proliferation (29). In our study, neutralization of IL-15 down-modulated SLA-induced IFN-γ secretion by PBMC from CL patients but had a weaker effect on PBMC from ML patients.…”
Section: Discussionmentioning
confidence: 99%
“…IL-15 induces lymphocyte proliferation and protects cells from apoptosis, thereby generating memory T cells (28) and anti-IL-15 can down-modulate lymphocyte proliferation (29). In our study, neutralization of IL-15 down-modulated SLA-induced IFN-γ secretion by PBMC from CL patients but had a weaker effect on PBMC from ML patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in some studies, IL-15 (Immunex) and IL-12 (R&D Systems) were used at concentrations suggested in the literature. 24,25 For the studies, CD8 ϩ cells were either left unstimulated or stimulated with both anti-CD3 and anti-CD28 antibodies (R&D Systems). 23 The anti-CD3 antibodies (1 g/mL) were bound to 96-well round bottom plates for 2 hours at 37°C, washed twice with phosphate-buffered saline (PBS), and CD28 antibodies (1 g/mL) were then added.…”
Section: Subset Isolation and Cell Culturementioning
confidence: 99%
“…5 Culture supernatants were assayed for reverse-transcriptase (RT) activity on days 5 and 7. 24 The extent (percent) of CNAR was determined by comparing the average percentage of RT activity in supernatants from duplicate cocultures with the average RT activity in fluids from HIV-infected CD4 ϩ cells cultured alone. Bars indicate average suppression resulting from each treatment.…”
Section: Monocyte-derived Dendritic Cells Enhance Cnar In Hiv-infectementioning
confidence: 99%
“…This suggests that the observed deficiency in the measles-specific T-cell responses in infants is a more complex limitation of infant immune cells, likely to include other key cytokines. Like IL-12, IL-15 is an important cytokine made by activated antigen-presenting cells (APCs), which has both T-and B-cell stimulatory activity (30,43). Decreased IL-15, along with low IL-12 production, would decrease humoral immune responses as well as adaptive T-cell immunity, both of which are seen in infants immunized with measles vaccine.…”
Section: Introduction M Easles Remains a Substantial Cause Of Globalmentioning
confidence: 99%